2014
DOI: 10.1021/es502655m
|View full text |Cite
|
Sign up to set email alerts
|

Energy’s Thirst for Water in China

Abstract: Water scarcity and uneven water distribution pose significant challenges to sustainable development and energy production in China. Based on the International Energy Agency (IEA)'s energy strategy scenarios for China, we evaluated the water withdrawal for energy production from 2011 to 2030. The results show that the amount of water withdrawal will be increased by 77% in 2030, which will aggravate China's water scarcity risk under current energy strategy. We also observed that 67% of the energy production in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Currently, water shortage is the greatest problem in China, where the average water use per capita is 2200 m 3 [8]. The distribution of water resources in the country has exacerbated a water crisis in northwestern China [9]. The central government has set a target that the entire nation will be poverty-free in 2020, which would severely restrict water use [10].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, water shortage is the greatest problem in China, where the average water use per capita is 2200 m 3 [8]. The distribution of water resources in the country has exacerbated a water crisis in northwestern China [9]. The central government has set a target that the entire nation will be poverty-free in 2020, which would severely restrict water use [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that the pattern of the monthly streamflow change due to damming is location-dependent [7,13,49,50]. In China, the accelerating development of economy increases the demand for energy and water resource, thus raising the need for the hydraulic engineering facilities, such as dams and reservoirs [51]. So far, most studies have focused on the impacts of large dams in large basins of China including Yangtze River and Yellow River [12,26,48,52,53].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study considered their water use factors to be zero, which is also used in the previous studies of operational water use for electricity generation in China [20,36], the United States [6], the United Kingdom [5], India [16] and globally [15]. For hydropower generation, water is consumed through evaporation from a reservoir's surface.…”
Section: Datamentioning
confidence: 99%